Determinant auditor switching pada perusahaan terdampak Covid-19 yang terdaftar di Bursa Efek Indonesia tahun 2017-2021 - Adityaningrum, Utami; Yendrawati, Reni (Proceeding of National Conference on Accounting & Finance, 2024)
This study aims to determine the effect of audit opinion, financial distress, management change and firm size on auditor switching. This study uses a quantitative model with data collection methods using purposive sampling of companies effected by Covid-19 there for: health company, insurance company, logistics company telecomunication cmpany listed on the BEI for period 2017-2021. There are 46 companies and 230 samples. The results of this study indicate that: 1) It is proven that opinion audit has a positive effect on auditor switching 2) financial distress has a positive effect on auditor switching 3) company size has been proven to have a negative effect on auditor switching; 4) management change has no effect on auditor switching.